2017
DOI: 10.3389/fnagi.2017.00238
|View full text |Cite
|
Sign up to set email alerts
|

Dl-3-n-Butylphthalide Treatment Enhances Hemodynamics and Ameliorates Memory Deficits in Rats with Chronic Cerebral Hypoperfusion

Abstract: Our previous study has revealed that chronic cerebral hypoperfusion (CCH) activates a compensatory vascular mechanism attempting to maintain an optimal cerebral blood flow (CBF). However, this compensation fails to prevent neuronal death and cognitive impairment because neurons die prior to the restoration of normal CBF. Therefore, pharmacological invention may be critical to enhance the CBF for reducing neurodegeneration and memory deficit. Dl-3-n-butylphthalide (NBP) is a compound isolated from the seeds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 45 publications
5
54
0
Order By: Relevance
“…Production of pro‐inflammatory cytokines like TNFα and IL‐6 was also decreased in LPS‐treated astrocytes in vitro by NBP. Consistent with our results, NBP has been demonstrated to inhibit neuroinflammation in several neurological diseases, including ischemic stroke, multiple sclerosis, AD, and vascular dementia . NBP administration inhibited reactive astrogliosis and ameliorated cognitive deficits in rats with VCI due to chronic cerebral hypoperfusion induced by bilateral common carotid artery occlusion .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Production of pro‐inflammatory cytokines like TNFα and IL‐6 was also decreased in LPS‐treated astrocytes in vitro by NBP. Consistent with our results, NBP has been demonstrated to inhibit neuroinflammation in several neurological diseases, including ischemic stroke, multiple sclerosis, AD, and vascular dementia . NBP administration inhibited reactive astrogliosis and ameliorated cognitive deficits in rats with VCI due to chronic cerebral hypoperfusion induced by bilateral common carotid artery occlusion .…”
Section: Discussionsupporting
confidence: 91%
“…Studies have demonstrated that NBP exerts multi‐target protective effects against ischemic stroke, including reducing oxidative stress, inhibiting inflammatory responses, alleviating neuronal apoptosis, ameliorating BBB damage, and increasing regional blood flow . Moreover, emerging evidence indicates that NBP also have beneficial effects on cognitive function of Alzheimer's Disease (AD) and vascular dementia, through regulating endoplasmic stress, reducing neuronal apoptosis, and glial reactivity …”
Section: Introductionmentioning
confidence: 99%
“…Dl‐3‐n‐butylphthalide is a drug developed independently for the treatment of ischemic stroke in China, which is an effective component obtained from celery seeds (Tian, Wang, Wang, Zhang, & Zhou, ; Xiong et al, ), and it can be artificially synthesized. Some Chinese scholars (Wang, Ma, et al, ) have summarized the research progress of NBP in the treatment of ischemic stroke in the past 20 years, and it was considered as a promising drug for ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Dl-3-n-butylphthalide is a drug developed independently for the treatment of ischemic stroke in China, which is an effective component obtained from celery seeds (Tian, Wang, Wang, Zhang, & Zhou, 2017;Xiong et al, 2017), and it can be artificially synthesized.…”
Section: Ta B L E 1 Comparison Of Clinical Efficacy Between Two Groupmentioning
confidence: 99%
“…Beclin1 plays an important role in this network interaction. 41 Our previous studies have reported that rats treated with Dl-NBP improved locomotor recovery after SCI by inhibiting ER stress-induced apoptosis, which lasts 28 days. 40 Traumatic brain injury causes activation of mitochondrial apoptosis.…”
Section: Discussionmentioning
confidence: 98%